2020
DOI: 10.1111/ijac.13622
|View full text |Cite
|
Sign up to set email alerts
|

Development of cordierite/mullite composites using industrial wastes

Abstract: 1 | INTRODUCTION Cordierite (2MgO•2Al 2 O 3 •5SiO 2) is one of the most important phases of the MgO-SiO 2-Al 2 O 3 system, having a low coefficient of thermal expansion, excellent thermal shock resistance, low dielectric constant, high resistivity, high chemical resistance, high refractoriness, and high mechanical strength. 1-7 Cordierite-based materials are used in various industrial fields in applications such as refractories, heat insulation, filters, membranes, heating elements, microwave and electromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In the case of coarser aggregates (RC4), an evident mass loss of 5.3% was observed ( Figure 1 b). The slight exothermic peak at about 800 °C (RB3) was related to the formation of enstatite and amorphous silicate [ 26 ]. Around 970 °C, the presence of mullite crystals, kalsilite, leucite and spinel could be justified by the appearance of an exothermic phenomena (RB1).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of coarser aggregates (RC4), an evident mass loss of 5.3% was observed ( Figure 1 b). The slight exothermic peak at about 800 °C (RB3) was related to the formation of enstatite and amorphous silicate [ 26 ]. Around 970 °C, the presence of mullite crystals, kalsilite, leucite and spinel could be justified by the appearance of an exothermic phenomena (RB1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Pinheiro de Brito et al [138] reported the synthesis of cordierite-mullite composites, suitable for application as refractory materials, from compositions incorporating kaolin wastes together with talc and magnesium hydroxide wastes. ) as crystalline phases.…”
Section: Kaolin Processing Wastementioning
confidence: 99%
“…Cordierite (2MgO•2Al 2 O 3 •5SiO 2 ) is a promising material for the probe card substrate due to its attractive properties, which include high thermal shock resistance, high resistivity, high refractoriness, chemical stability, and low TEC. As a result, cordierite has found widespread use in a variety of applications, including electrical insulators, refractories, filters, membranes, integrated circuit board substrates, and microwaves [5][6][7][8]. However, dense cordierite ceramics are difficult to obtain due to cordierites' narrow sintering temperature and difficulty sintering using the solid-state process [9][10][11].…”
Section: Introductionmentioning
confidence: 99%